Compliance e corrupção: uma análise da integração de stakeholders fornecedores nos programas de compliance das organizações públicas federais - Stoever, Carlos Alberto Day (2022)
Concern about integrity in organizations is a growing theme in Brazil. The matter has been gaining importance since Operation Car Wash, which affected the largest companies in the country, uncovering a large corruption scheme involving public contracts. Since then, compliance programs have been gaining support from public organizations, largely due to the demands made by external control bodies. However, the compliance programs of public bodies are still focused on their internal audience, not having a broad scope, to map and involve all their stakeholders. Within this scenario, the present work seeks to analyze the relationship between the compliance programs applied to supplier stakeholders and the level of corruption of public organizations, identifying whether and how this relationship reflects on the Fraud and Corruption Control Fragility Index calculated by the Court of Justice. Union Accounts. Using stakeholder theory as a theoretical basis for research and advancing its relationship with compliance programs, the work explores corruption in organizations as a result of both constructs. Afterwards, a qualitative analysis is made of how the compliance programs of public organizations affect their suppliers. Using comparative qualitative analysis, it is explored whether there is a relationship with the Fraud and Corruption Controls Weakness Index. In the end, eight models of compliance program configurations applicable to supplier stakeholders were found. Among them, three compositions were identified that have sufficient consistency to result in a higher fraud and corruption control fragility index. In these, the performance of due diligence by public organizations was observed as a central element.